2017
DOI: 10.1080/02713683.2017.1297995
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Toxicity of Acai Fruit (Euterpe Oleracea) Dye Concentrations in Rabbits: Basic Principles of a New Dye for Chromovitrectomy in Humans

Abstract: Ten and twenty-five percent concentrations were safe and may improve identification of the posterior hyaloid and internal limiting membrane during chromovitrectomy in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…A total of 60 publications were identified in the databases; however, 31 were duplicate articles. Among the 29 articles selected, 20 were excluded based on the titles and abstracts because they did not meet the inclusion criteria: 2 were literature reviews [ 7 , 24 ]; 6 did not study açaí in an animal model of cancer and/or did not perform a toxicological analysis [ 25 30 ]; 10 were in vitro studies [ 13 , 20 , 31 38 ]; and 2 did not use the order Rodentia [ 21 , 39 ]. After reading the full texts 9 articles were included for their critical evaluations of the safety and effectiveness of açaí in animal experimental models [ 40 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 60 publications were identified in the databases; however, 31 were duplicate articles. Among the 29 articles selected, 20 were excluded based on the titles and abstracts because they did not meet the inclusion criteria: 2 were literature reviews [ 7 , 24 ]; 6 did not study açaí in an animal model of cancer and/or did not perform a toxicological analysis [ 25 30 ]; 10 were in vitro studies [ 13 , 20 , 31 38 ]; and 2 did not use the order Rodentia [ 21 , 39 ]. After reading the full texts 9 articles were included for their critical evaluations of the safety and effectiveness of açaí in animal experimental models [ 40 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…To date, açaí has been shown to have pharmacological properties including antiinflammatory, antioxidant, cardioprotective and anticancer activities [ 1 , 7 9 , 18 , 19 ]. Furthermore, açaí was not shown to be genotoxic in vitro and in vivo studies conducted, in cultured human lymphocytes and hepatoma cell lines [ 20 ], in rodents [ 21 ] and in humans [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lyophilized dye solutions were stored in depyrogenized amber flasks based on our previous results that anthocyanin molecules are highly unstable and light exposure might modify the staining capacity of the dye [ 9 ]. The anthocyanins were then analytically characterized by mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%
“…In 2017, our research group found that the 10% and 25% concentrations of the acai dye were safe when used in a rabbit model [ 9 ]. In this study, rabbits were injected intravitreously with the acai dye in three concentrations: 10%, 25%, and 35%.…”
Section: Introductionmentioning
confidence: 99%
“…Acai fruit is the most promising of a group of naturally occurring dyes that have recently been investigated. 117,118 It is a purple-colored anthocyanin dye that preferentially stains the ILM and recently underwent human trial (Clinicaltrials.gov: NCT02691429) with the results yet to be published.…”
Section: Investigational Dyesmentioning
confidence: 99%